Adamantyl-tethered-biphenylic compounds induce apoptosis in cancer cells by targeting Bcl homologs. Issue 3 (1st February 2016) - Anusha, Sebastian; Mohan, Chakrabhavi Dhananjaya; Ananda, Hanumappa; Baburajeev, C.P.; Rangappa, Shobith; Mathai, Jessin; Fuchs, Julian E.; Li, Feng; Shanmugam, Muthu K.; Bender, Andreas; Sethi, Gautam; Basappa,; et al.
Graphical abstract: Abstract: Bcl homologs prominently contribute to apoptotic resistance in cancer cells and serve as molecular targets in treatment of various cancers. Herein, we report the synthesis of biphenyl-adamantane derivatives by a ligand free palladium on carbon based Suzuki reaction using diisopropylamine as a base for the coupling of adamantane based aryl chloride with a variety of aryl boronic acids. Among the biphenyl derivatives synthesized, compound 3′-(adamantan-1-yl)-4′-methoxy-[1, 1′-biphenyl]-3-ol (AMB) displayed cytotoxic activity against hepatocellular carcinoma cell lines without significantly affecting the normal cell lines. Further, AMB caused increased accumulation of the HCC cells in subG1 phase, decreased the expression of Bcl-2, Bcl-xL, cyclin D1, caspase-3, survivin and increased the cleavage of PARP in a time-dependent manner. In silico molecular interaction studies between Bcl homologs and AMB showed that the biphenyl scaffold is predicted to form π–π interactions with Phe-101 and Tyr-105 and the adamantyl fragment is predicted to occupy another hydrophobic region in the kink region of the binding groove. In summary, we report on the synthesis and biological characterization of adamantyl-tethered biphenylic compounds that induce apoptosis in tumor cells most likely by targeting Bcl homologs.